A Comprehensive Review of Fault Location Methods for Distribution Power System - N Gana; NF Ab Aziz; Z Ali; H Hashim; Bahisham Yunus (Institute of Advanced Engineering and Science, 2017)
Fault on distribution system does not only affect the reliability of power supply, but also contribute to increasing operational and maintenance cost borne by the utilities. Throughout the years, various methods have been studied and practiced to solve problems related to the fault location in the distribution system. In this paper, the fault location methods are reviewed and summarised according to their categories. The fault location methods discussed in this paper are based on literature studies of outage mapping and field measurement for the distribution system. Furthermore, the component which influences the fault location methods such as unbalanced system, capacitance effects, distributed generation, and distribution topology are related to the explanation of the method. Finally, the field measurements are presented as in comparison which will clarify the effectiveness and the establishment of each method.